Responding to Anxiety with Rumination and Hopelessness: Mechanism of Anxiety-Depression Symptom Co-Occurrence? - Starr, Lisa R. (2012)
The current research proposes that certain anxiety response styles (specifically, responding to anxiety symptoms with rumination or hopeless cognitions) may increase risk of depressive symptoms, contributing to anxiety-depression comorbidity. We delineate preliminary evidence for this model in three studies. In Study 1, controlling for anxiety response styles significantly reduced the association between anxiety and depressive symptoms in an undergraduate sample. In Study 2, these findings were replicated controlling for conceptually related variables, and anxiety interacted with anxiety response styles to predict greater depressive symptoms. In Study 3, anxiety response styles moderated the prospective association between anxiety and later depression in a generalized anxiety disorder sample. Results support a role for anxiety response styles in anxiety-depression co-occurrence, and show that hopeless/ruminative anxiety response styles can be measured with high reliability and convergent and divergent validity.